1995
DOI: 10.1128/jb.177.4.877-882.1995
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the cell envelope of Chlamydia psittaci 6BC

Abstract: The cysteine-rich envelope proteins of the elementary body form of chlamydiae are thought to be located in the outer membrane on the basis of their insolubility in the weak anionic detergent N-lauryl sarcosinate (Sarkosyl). We found, however, that the insolubility of the small (EnvA) and the large (EnvB) cysteine-rich proteins of Chlamydia psittaci 6BC in Sarkosyl is dependent on the maintenance of a supramolecular disulfidecross-linked complex and is unlikely to be a valid indicator of outer membrane location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 34 publications
8
84
1
Order By: Relevance
“…How it breaches this compartment is unclear, given its hypothesized function. OmcB and OmcA (9-kDa cysteine-rich protein) are postulated to reside in the periplasmic space of EBs and to be functionally associated with the outer membrane complex (41). Both OmcB and OmcA contain numerous cysteine residues and, along with MOMP, may confer rigidity and osmotic integrity to chlamydial EBs by creating a lattice of disulfide bond cross-linked structure, forming the functional equivalent of peptidoglycan (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…How it breaches this compartment is unclear, given its hypothesized function. OmcB and OmcA (9-kDa cysteine-rich protein) are postulated to reside in the periplasmic space of EBs and to be functionally associated with the outer membrane complex (41). Both OmcB and OmcA contain numerous cysteine residues and, along with MOMP, may confer rigidity and osmotic integrity to chlamydial EBs by creating a lattice of disulfide bond cross-linked structure, forming the functional equivalent of peptidoglycan (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…These cysteine-rich proteins are sensitive to the redox state of the environment and they might provide some rigidity and resistance to osmotic pressure through the formation of disulfide bridges. Some authors suggested that they may replace the peptidoglycan layer present in the periplasm of other Gram-negative bacteria (Everett & Hatch, 1995;Sun et al, 2007). No homologs of OmcA and OmcB were identified in S. negevensis genome and none of the identified MOMP-like proteins could serve this function as their content in cysteine was extremely low (Aistleitner et al, 2015).…”
Section: Cell Wall and Surface Proteinsmentioning
confidence: 99%
“…Human diseases attributed to C. pneumoniae include atypical pneumoniae, bronchitis, otitis media, and perhaps arteriosclerosis (5). Structurally, C. pneumoniae displays a cell wall similar to that of Gram-negative bacteria (6). However, two important differences exist.…”
mentioning
confidence: 99%